Early signs of right ventricular systolic and diastolic dysfunction in acute severe respiratory failure: the importance of diastolic restrictive pattern - Tavazzi, Guido (Eur Heart J Acute Cardiovasc Care, 2019)
BACKGROUND: The incidence and pathophysiology of right ventricular failure in patients with severe respiratory insufficiency has been largely investigated. However, there is a lack of early signs suggesting right ventricular systolic and diastolic dysfunction prior to acute cor pulmonale development. METHODS: We conducted a retrospective analytical cohort study of patients for acute respiratory distress syndrome undertaking an echocardiography during admission in the cardiothoracic intensive care unit. Patients were divided according to treatment: conventional protective ventilation (38 patients, 38%); interventional lung assist (23 patients, 23%); veno-venous extracorporeal membrane oxygenation (37 patients, 37%). Systolic and diastolic function was studied assessing, respectively: right ventricular systolic longitudinal function (tricuspid annular plane systolic excursion) and systolic contraction duration (tricuspid annular plane systolic excursion length); right ventricular diastolic filling time and right ventricular diastolic restrictive pattern (presence of pulmonary valve presystolic ejection wave). Correlation between the respiratory mechanics and systo-diastolic parameters were analysed. RESULTS: In 98 patients studied, systolic dysfunction (tricuspid annular plane systolic excursion <16 mm) was present in 33.6% while diastolic restrictive pattern was present in 64%. A negative correlation was found between tricuspid annular plane systolic excursion and tricuspid annular plane systolic excursion length (P<0.0001; r −0.42). Tricuspid annular plane systolic excursion and tricuspid annular plane systolic excursion length correlated with right ventricular diastolic filling time (P<0.001; r −0.39). Pulmonary valve presystolic ejection wave was associated with tricuspid annular plane systolic excursion (P<0.0001), tricuspid annular plane systolic excursion length (P<0.0001), right ventricular diastolic filling time (P<0.0001), positive end-expiratory pressure (P<0.0001) and peak inspiratory pressure (P<0.0001). CONCLUSION: Diastolic restrictive pattern is present in a remarkable percentage of patients with respiratory distress syndrome. Bedside echocardiography allows a mechanistic evaluation of systolic and diastolic interaction of the right ventricle.